Using Polypropylene Bags for Long-Term Storage of Smoked Dried Freshwater Garfish Xenentodon cancila (Hamilton, 1822) - Tepmuangkhun, Junsuda; somsamorn, Gawborisut (Journal of Fisheries and Environment, 2021)
Smoked dried freshwater garfish Xenentodon cancila (Hamilton, 1822), a high-priced delicacy, is manufactured by small-scale smoked fish producers in Thailand. The traditional method of storage of smoked dried freshwater garfish (SDFG) involves stacking the product in plastic or bamboo threshing baskets, leaving the SDFG exposed to atmospheric moisture, which is absorbed by the product, causing mould proliferation and a short shelf life. Our experiment aimed to minimise deterioration of the product by keeping the SDFG in polypropylene bags, an affordable option recommended for packing dried foods. The experiment compared food-quality parameters of SDFG stored using the traditional method (TM) to those of SDFG stored in polypropylene bags (PP). SDFG samples kept in TM and PP were sampled at 0, 2, 4, and 6 months and evaluated for yeast and mould count (YM), total plate count (TPC), thiobarbituric acid reactive substances (TBARS), non-enzymatic browning, water activity (aw), moisture content, CIE colour values (L*, a*, and b*), and sensory scores (general appearance, colour, odour, and taste). The results showed that PP yielded lower YM, TPC, non-enzymatic browning, aw and moisture content compared to TM; thus, PP provided better storage. PP also provided a higher L* value in month 6 compared to TM, indicating a brighter coloured product. PP scored higher in general appearance and colour compared to TM. However, PP and TM were not significantly different in terms of TBARS, odour, or taste. In conclusion, PP offered better protection and is recommended for long-term storage of SDFG.